Glycine Transporter Blockade Ameliorates Motor Ataxia in a Mouse Model of Spinocerebellar Atrophy - Mitsuo Tanabe; Tomoharu Nakano; Motoko Honda; Hideki Ono (Journal of Pharmacological Sciences, 2009)
Ataxic movement, the common major symptom of spinocerebellar atrophy, has been considered to involve impaired glutamatergic excitatory neurotransmission in the cerebellum. Considering the therapeutic importance of ataxia control, we assessed the effectiveness of increasing the extracellular concentration of glycine by administering it exogenously or via blockade of glycine transporter 1, using its selective inhibitors sarcosine and N-[3-(4’-fluorophenyl)-3-(4’-phenylphenoxy)propyl]sarcosine (NFPS), for amelioration of motor ataxia in a mouse model of spinocerebellar atrophy developing after neonatal treatment with cytosine β-D-arabinofuranoside. Intracerebroventricular (i.c.v.) injection of sarcosine (3, 10, and 30 μg) and NFPS (0.01 and 0.03 μg) reduced the number of falls without affecting spontaneous motor activity, and therefore the falling index [(number of falls / spontaneous motor activity) × 100], and dose-dependently ameliorated ataxic movements. Similar effects were observed upon i.c.v. injection of D-serine (1 and 10 μg), an agonist of the glycine-recognition site of the N-methyl-D-aspartate (NMDA) receptor. However, exogenously injected glycine (1, 3, and 10 μg, i.c.v.) only weakly ameliorated the ataxic movements at 3 μg. These results suggest the therapeutic relevance of GlyT1 inhibitors for amelioration of motor ataxia in spinocerebellar atrophy by increasing the endogenous concentration of glycine near the glycine-recognition site of the NMDA receptor. Keywords:: motor ataxia, spinocerebellar atrophy, glycine, D-serine, glycine transporter